Synthesis of poly(ionic liquid) for trifunctional epoxy resin with simultaneously enhancing the toughness, thermal and dielectric performances. Issue 4 (10th January 2020) - Yin, Bingyan; Xu, Wenqing; Liu, Chengjun; Kong, Miqiu; Lv, Yadong; Huang, Yajiang; Yang, Qi; Li, Guangxian
Abstract : This work will provide a strategy to obtain epoxy with relatively high toughness, thermal and dielectric properties. Abstract : Poly(ionic liquid) (PIL), integrating the characteristics of both polymers and ionic liquid, is synthesized and employed to modify diglycidyl-4, 5-epoxy-cyclohexane-1, 2-dicarboxylate (TDE-85). With the addition of PIL, the fracture toughness, and thermal and dielectric performances of TDE-85 were discovered to be simultaneously improved, meanwhile the tensile modulus and strength is increased. Upon an optimal loading of 3 wt% PIL, the critical stress intensity factor ( K IC ), tensile modulus and strength are raised by 92.9%, 13.3% and 10.7%, respectively. Multi-toughening mechanisms due to spherical domains of PIL formed in TDE-85 during curing are responsible for the improved toughness. Moreover, the dielectric and thermal properties of TDE-85 are also enhanced by adding PIL. With the optimal addition of 5 wt% PIL, the dielectric constant of the composites is enhanced by 62.5%, the glass transition temperature is increased by 16.58 °C and the residual weight of carbon is increased by 59%.